2021
DOI: 10.1177/1941738121999047
|View full text |Cite
|
Sign up to set email alerts
|

Fear Avoidance After Injury and Readiness to Return to Sport in Collegiate Male and Female Gaelic Games Players

Abstract: Background: Injuries are common in collegiate Gaelic games, and negative psychological responses to injury, such as fear avoidance and a lack of psychological readiness to return to sport, can affect players during their rehabilitation and their subsequent return to sport. Thus, identifying these responses in players can allow clinicians to address these issues during rehabilitation. This study aimed to examine fear avoidance and psychological readiness to return to sport in collegiate Gaelic games players. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
2
7
0
1
Order By: Relevance
“…Psychometric testing demonstrated good internal consistency and acceptable concurrent validity, as assessed through established measures of fear-avoidance and catastrophizing [15]. Despite clinical use of this tool in different countries [9,13,16,17], to our knowledge, no psychometric validation of the AFAQ in a language other than English has been indexed in PubMed. Considering the importance of collecting athletes' experience in this clinical area, we aimed to develop a culturally adapted and validated Italian version of the AFAQ for assessing fear-avoidance beliefs in Italian athletes with musculoskeletal injuries engaged in both team and individual sports.…”
Section: Introductionmentioning
confidence: 99%
“…Psychometric testing demonstrated good internal consistency and acceptable concurrent validity, as assessed through established measures of fear-avoidance and catastrophizing [15]. Despite clinical use of this tool in different countries [9,13,16,17], to our knowledge, no psychometric validation of the AFAQ in a language other than English has been indexed in PubMed. Considering the importance of collecting athletes' experience in this clinical area, we aimed to develop a culturally adapted and validated Italian version of the AFAQ for assessing fear-avoidance beliefs in Italian athletes with musculoskeletal injuries engaged in both team and individual sports.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study by O’Connor et al found that approximately half of all GAA players consider themselves not to be psychologically ready to RTP, despite being cleared clinically. 24 With all factors considered, the authors believe that perhaps consensus to inform on criteria for RTP in GAA games after surgical stabilization would be of benefit to both orthopedic surgeons in future.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Previous literature has reported that the incidence of injury for GAA athletes may be as high as 61 injuries per 1000 match hours, with lower limb injuries representing the most common injuries seen in GAA players. 21 , 23 , 24 However, similar to other collision sports, shoulder injuries commonly occur during GAA games particularly while tackling or reaching for the ball overhead, as the shoulder is commonly forced into abduction and external rotation, representing a harbinger for potential anterior shoulder instability. 3 The high incidence of injuries among GAA athletes is not without morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…During rehabilitation or even after being completely healed, athletes may develop a fear of re-injury thus the need for addressing it during rehabilitation. During rehabilitation, an injured athlete may experience fear avoidance, which, in turn, may cause behaviors that adversely impacts their recovery [12]. Nonetheless, if fear is noted early, it can be addressed promptly to avoid a negative effect on recovery.…”
Section: Psychological Rehabilitation Of Re-injury Fearmentioning
confidence: 99%
“…Nonetheless, if fear is noted early, it can be addressed promptly to avoid a negative effect on recovery. Consequently, a player may not be psychologically ready to return to the sport after complete healings fear avoidance and low confidence issues emerge [12]. The fear of re-injury, in turn, brings about adverse outcomes.…”
Section: Psychological Rehabilitation Of Re-injury Fearmentioning
confidence: 99%